Pendampingan Pendataan Santri Berbasis Komputerisasi Di Pondok Pesantren Darul Ilmi - Destiartono, Mohamad Egi; Darwanto; Kafabih, An’im; Santosa, Purbayu Budi; Maria, Nugroho Nugroho Sumarjiyanto Benedictus (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2024)
Data play an important role in mapping problems, potentials, and long-term plans of an institution, including Islamic boarding schools. This Community Service (PKM) activity aims to socialize the importance of computer-based data management through the use of Microsoft Excel, Google Forms, and Bitly. This community service activity was carried out at the Darul Ilmi Islamic boarding school, Meteseh Village, Semarang. Community service was conducted through three approaches: (i) field observation, (ii) interactive socialization, and (iii) mentoring/training. Field observations were applied to collect problems that existed at the location and potential that could be developed. Socialization was carried out by providing material on "the importance of computer-based data management" to increase the efficiency and effectiveness of the use of student data. Interactive socialization was employed directly to provide space for all participants to express their opinions. The results of this PKM were three things: (i) mentoring the use of M.S. Excel for data management; (ii) training in the use of Google Forms to collect student data according to certain objectives, for example, biodata and future career plans; and (iii) educating the application of Bit.ly as a device to shorten and manage URLs.